Administrative Sciences and their Origin in Ancient Corinth (*) - Kantarelis, Demetri (Archives of Business Research, 2023)
During Periander’s reign (c. 627–585 BCE), Corinth became the wealthiest city-state in pre-classical Ancient Greece. By relying on reviewing ancient and non-ancient writings about Ancient Corinth, I venture to claim that Periander invented the multi-divisional form of organization. Additionally, I claim that he deserves to be called the Father of Administrative Sciences because, in his attempt to manage the city-state (his organization) efficiently and effectively, he instituted adverse selection and moral hazard minimizing incentive mechanisms. Periander established a classless society and encouraged the creation of new products and services. He promoted competition, efficiency, and fairness. He was against free monopoly and opportunism of any short as well as against waste and luxury. He freed all slaves so that Corinthians focus less on inconsequential endeavors and more on how to sharpen skills and improve know-how to enrich their lives and their city-state. He enabled Corinthians to distribute their products all over the known world by relying on sea trade and trade centers (primary Corinthian colonies) and marketed his city-state products through effective marketing by relying, mainly, on diplomacy. He minted state-sponsored metal coin money which became the most popular medium of exchange in trade dealings across the Mediterranean Basin. Furthermore, he required sellers to issue receipts and pay taxes above a certain level of revenue. Undoubtedly, during Periander’s 40 years of reign, materially, culturally, and aesthetically, Ancient Corinth became the Shining City on a Hill.